PATIENT SAFETY IN THE HOSPITAL CONTEXT: AN INTEGRATIVE LITERATURE REVIEW - Andréia Cristina Araújo Silva; Jéssica Fontinele da Silva; Lidyane Rodrigues Oliveira Santos; Fernanda Valéria Silva Dantas Avelino; Ana Maria Ribeiro dos Santos; Antônio Francisco Machado Pereira (Universidade Federal do Paraná, 2016)
This integrative review aimed to identify the main patient safety issues addressed in the hospital context. The search occurred in three electronic databases, covering the period 2009 to 2015, with the following descriptors: "Patient safety", "Risk control" and "Hospitalization". The study sample consisted of 34 articles. There was a significant increase in the number of publications on the subject in 2013, more than 100% compared to the year 2009. Of the studies, 22.22% dealt with adverse events and 18.52% with errors in the administration of medication. Among preventive measures, 37.93% highlighted continuing education and 13.79% handwashing and the correct identification of the patient. The strategic option for safety has been included in the agendas of health institutions, organizations and systems as a priority. Therefore, it is suggested to expand the focus of research to improve the quality of care.